Trans-chalcone increases p53 activity via DNAJB1/HSP40 induction and CRM1 inhibition - Silva, Gabriel; Marins, Mozart; Chaichanasak, Nadda; Yoon, Yongdae; Fachin, Ana Lucia; Pinhanelli, Vitor Caressato; Regasini, Luis Octavio [UNESP]; Santos, Mariana Bastos dos [UNESP]; Ayusso, Gabriela Miranda [UNESP]; Marques, Beatriz de Carvalho [UNESP]; Wu, Wells W.; Phue, Je-Nie; et al. (Public Library Science, 2018)
Naturally-occurring chalcones and synthetic chalcone analogues have been demonstrated to have many biological effects, including anti-inflammatory, anti-malarial, anti-fungal, and anti-oxidant/anti-cancerous activities. Compared to other chalcones, trans-chalcone exhibits superior inhibitory activity in cancer cell growth as shown via in vitro assays, and exerts anti-cancerous effects via the activation of the p53 tumor suppressor protein. Thus, characterization of the specific mechanisms, by which trans-chalcone activates p53, can aid development of new chemotherapeutic drugs that can be used individually or synergistically with other drugs. In this report, we found that trans-chalcone modulates many p53 target genes, HSP40 being the most induced gene in the RNA-Seq data using trans-chalcone-treated cells. CRM1 is also inhibited by trans-chalcone, resulting in the accumulation of p53 and other tumor suppressor proteins in the nucleus. Similar effects were seen using trans-chalcone derivatives. Overall, trans-chalcone could provide a strong foundation for the development of chalcone-based anti-cancer drugs.